Investigating Learning Technology By Design Approach in Pre-Service Language Teacher Education: Collaborative and Reflective Experiences - Asuman Aşık; Burtay Hatice Eroğlu İnce; Arzu Şarlanoğlu Vural (Anı Publishing, 2018)
The study aims to present how technology integration can be fulfilled into Language Teacher Education (LTE) contexts by tracking the development of Technological Pedagogical Content Knowledge (TPACK) of the pre-service English Language teachers through Learning Technology By Design approach. A total of 100 senior student teachers (STs) of English at a large state university in Turkey participated in the study. The STs were required totrain their peers about one digital tool and prepare digital materials to be used in language classrooms. The data were collected through three instruments quantitatively and qualitatively: the TPACK-EFL survey, peer reflective discussion forms and focus-group interviews. The findings revealed that the TPACK-EFL knowledge of the STs has improved significantly in all domains after the research intervention, and the STs reported considerably positive perceptions about the digital tools such as increasing motivation and positive atmosphere, more attractive and content-rich materials and more practical and found the experience of peer teaching very effective. The study suggests implications for a variety of digital tools to be used in language classrooms and aneffective technology training in LTE contexts.